2014
DOI: 10.1002/ajh.23798
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab–cyclophosphamide‐dexamethasone is highly effective in patients with monoclonal Ig deposit‐related glomerulopathy and indolent non‐Hodgkin lymphomas

Abstract: Indolent non-hodgkin lymphomas (iNHL) are a rare cause of monoclonal immunoglobulin deposits-related glomerulopathy (mIgGN). In patients with iNHL-related mIgGN, whether treatment should include either single or a combination of drug(s) to target the malignant clone and renal inflammation remains elusive. In this retrospective study, we report a cohort of 14 patients with iNHL-related mIgGN (cryoglobulinemic glomerulonephritis [n 5 5], membranous nephropathy [n 5 3], membranoproliferative glomerulonephritis [n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
(37 reference statements)
2
4
0
2
Order By: Relevance
“…These results agree with those obtained in previous cohorts of patients with de novo or relapsing LPL, in which BR led to a ≈70 to 75% hematological response, but only to a 7 to 40% complete response . In this subtype of B‐cell lymphoma, whether combined rituximab–cyclophosphamide–dexamethasone therapy should be preferably given to patients with proliferative glomerulonephritis (i.e., at risk of rapid renal progression) should be addressed in a larger cohort. Indeed, for patients with hematological malignancies and related renal diseases, the choice of treatment should be based on both the awaited hematological response but also the characteristics of the nephropathy, which may need an urgent renal response.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results agree with those obtained in previous cohorts of patients with de novo or relapsing LPL, in which BR led to a ≈70 to 75% hematological response, but only to a 7 to 40% complete response . In this subtype of B‐cell lymphoma, whether combined rituximab–cyclophosphamide–dexamethasone therapy should be preferably given to patients with proliferative glomerulonephritis (i.e., at risk of rapid renal progression) should be addressed in a larger cohort. Indeed, for patients with hematological malignancies and related renal diseases, the choice of treatment should be based on both the awaited hematological response but also the characteristics of the nephropathy, which may need an urgent renal response.…”
Section: Discussionsupporting
confidence: 89%
“…Rituximab–cyclophosphamide–dexamethasone (RCD) is an efficient and safe combination that can target B‐cell malignant clones and reverse autoimmune‐related manifestations . Recently, we reported that this combination led to a complete hematological and renal response in 63% of patients with iNHL and mIg‐related glomerulonephritis . In this cohort, 21% of patients developed a bacterial infection requiring hospitalization (a higher rate than previously reported with RCD in autoimmune cytopenia) .…”
Section: Introductionmentioning
confidence: 81%
“…Indeed, cyclophosphamide and rituximab have been shown to be effective both in CLL and glomerulonephritis 30 31. Perry et al reported 14 patients affected by indolent non-Hodgkin lymphomas with monoclonal Ig deposit-related glomerulonephropathy: 63% and 64% of these patients had respectively a complete haematological and renal response following the combination of rituximab, cyclophosphamide and dexamethasone, respectively 32. Consistently, our patient achieved a complete haematological response and a good improvement of renal function, underlying the efficacy of this chemotherapy combination.…”
Section: Discussionsupporting
confidence: 82%
“…The physicochemical properties of the monoclonal immunoglobulin (rather than high rate of production) make it prone to be deposited in the kidney causing nephrotoxicity (“monoclonal gammopathy of renal significance” [MGRS]) and therefore warrants clone-directed treatment even though it does not meet the criteria for overt myeloma or lymphoma. There is as yet no consensus on treatment regimens for PGNMIGD, but few case series have demonstrated clinical remission with anti-B cell drug Rituximab, along with cytotoxic agent cyclophosphamide and dexamethasone [6, 7]. The unique feature in our case is the demonstration of complete resolution of the monoclonal IgG deposits from the kidney after treatment, demonstrated by serial follow up biopsies.…”
Section: Discussionmentioning
confidence: 77%
“…The disease is reported to recur and can also develop de novo in renal allografts [4, 5] and presentation is reported to be similar to that in the native kidney, with nephrotic range proteinuria and rapid deterioration of graft function. Several case series have shown clinical remission and decrease in proteinuria after immunosuppressive therapy with Rituximab (with or without cyclophosphamide) in native and in transplant kidney [4, 6, 7]. Herein we describe the first reported case of recurrent PGNMIGD in renal allograft with complete resolution of the monoclonal IgG3 kappa deposits after Rituximab, steroid and plasmapheresis therapy demonstrated by serial allograft biopsies mapping the entire histologic course of the disease.…”
Section: Introductionmentioning
confidence: 86%